(untitled) (Journal of Psychiatrists’ Association of Nepal, 2025)
Introduction: Sexual health significantly impacts the quality of life in cancer patients, yet no validated Nepali version of the EORTC Sexual Health Questionnaire (SHQ) exists. This study aimed to translate, culturally adapt, and validate the EORTC SHQ for use in Nepal. Materials and Methods: Following EORTC guidelines, the SHQ underwent forward and backward translation, expert review, and pilot testing. Ethical approval was obtained from the Institutional Review Committee of Nepal Cancer Hospital (IRC-NCHRC 008/2078), and informed consent was secured. A pilot sample of 50 Nepali cancer patients assessed feasibility and comprehensibility. Reliability and validity were analyzed statistically. Results: The translated SHQ was well understood, with no major issues reported. It demonstrated strong internal consistency, test-retest reliability, and construct validity, correlating significantly with quality of life and psychological distress measures. Conclusion: The validated Nepali SHQ is a reliable tool for assessing sexual health in Nepali cancer patients. Its availability will enhance understanding of cancer’s impact on sexual functioning and support targeted interventions.